2017
DOI: 10.1002/2016jd025987
|View full text |Cite
|
Sign up to set email alerts
|

Entrainment of stratospheric air and Asian pollution by the convective boundary layer in the southwestern U.S.

Abstract: A series of deep stratospheric intrusions in late May 2013 increased the daily maximum 8 h surface ozone (O3) concentrations to more than 70 parts per billion by volume (ppbv) at rural and urban surface monitors in California and Nevada. This influx of ozone‐rich lower stratospheric air and entrained Asian pollution persisted for more than 5 days and contributed to exceedances of the 2008 8 h national ambient air quality standard of 75 ppbv on 21 and 25 May in Clark County, NV. Exceedances would also have occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 69 publications
4
54
0
Order By: Relevance
“…Studies based on chemical transport models (CTMs) have shown that air quality in the U.S. can be considerably influenced by pollutants beyond the U.S. boundaries, such as through intercontinental transport, and through stratosphere-totroposphere exchange (Zhang et al, 2011;Lin et al, 2012;Nopmongcol et al, 2016;Langford et al, 2017;Lin et al, 2017;Hogrefe et al, 2017;Mathur et al, 2017). Similar findings have also been reported based on routine observations and field 5 campaign measurements (e.g.…”
Section: Introductionsupporting
confidence: 65%
“…Studies based on chemical transport models (CTMs) have shown that air quality in the U.S. can be considerably influenced by pollutants beyond the U.S. boundaries, such as through intercontinental transport, and through stratosphere-totroposphere exchange (Zhang et al, 2011;Lin et al, 2012;Nopmongcol et al, 2016;Langford et al, 2017;Lin et al, 2017;Hogrefe et al, 2017;Mathur et al, 2017). Similar findings have also been reported based on routine observations and field 5 campaign measurements (e.g.…”
Section: Introductionsupporting
confidence: 65%
“…There are generally insufficient data for characterizing these distributions for other parts of Asia, (Figure 4c-e). Higher ozone levels in the western US have been attributed to a number of factors, including intercontinental transport of Asian pollution, stratospheric intrusions and wildfires, as well as the combination of high elevations and an exceptionally deep convective boundary layer which allows high altitude ozone plumes to reach the surface (Lin et al, 2017;Langford et al, 2017). For SOMO35, there are more high values in non-urban (SOMO35 > 7000 ppb day = 45) compared to urban (SOMO35 > 7000 ppb day = 7) locations across the globe, and the percentage of SOMO35 values > 7000 is also higher for non-urban than urban sites (1.53% versus 0.50%).…”
Section: Distribution Of Present-day Ozone Metricsmentioning
confidence: 99%
“…Near the U.S. borders with Canada and Mexico, international pollution transport enhances USB O 3 relative to NAB O 3 (Wang et al, 2009;Guo et al, 2018). In the southwestern U.S., seasonal mean USB O 3 is higher than in other regions during both spring and summer, and NCOS play a more important role on high O 3 days (Fiore et al, 2014a;Langford et al, 2017), although stratospheric intrusions occasionally decrease surface O 3 in the heavily polluted Los Angeles Basin (Langford et al, 2012).…”
Section: Spatial and Temporal Distributions Of Usb Omentioning
confidence: 99%
“…These occur most frequently in winter when Rossby wave activity is at a maximum in the Northern Hemisphere, but the potential impact on surface O 3 is greater in late spring through early summer, when there is more O 3 in the lower stratosphere and deeper mixed layers can more easily entrain O 3 that reaches the lower troposphere (Langford et al, 2017). Descending stratospheric intrusions can also merge with biomass burning plumes (Brioude et al, 2007) or transported pollution (Cooper et al, 2004a, b;Lin et al, 2012b) and carry additional O 3 from these sources downward to the surface.…”
Section: Evidence For Ncos From Observations and Modelsmentioning
confidence: 99%
See 1 more Smart Citation